An overview of corona virus disease 19 - COVID 19 - Sharma, Sarita; Rathod, Pragati; Ukey, Ujwala (International Journal of Research in Medical Sciences, 2020)
A remerging infectious disease that has caught the entire world unaware. Coronavirus is an enveloped virus having non- segmented positive-sense RNA genome and belongs to the family Coronaviridae. Important modes of transmission are direct contact and respiratory droplets. Though the virus survives on environmental surfaces for varied period of time, it gets easily inactivated by chemical disinfectants .The major clinical features in uncomplicated cases include fever (88%), dry cough (67%), myalgia (14.9%) or fatigue (38%). In the absence of an effective treatment and vaccine, preventive measures like physical distancing, hand hygiene, following respiratory etiquettes & wearing mask assume great importance. Vigourous surveillance, contact tracing and containment can go a long way in controlling the spread of Covid 19.